MENINGKATKAN KREATIVITAS SISWA DALAM MEMANFAATKAN LIMBAH ALUMINIUM UNTUK KRIYA LOGAM DI SMA NEGERI 1 PANYABUNGAN UTARA - Syahril Firiyansyah; Amrizal Amrizal; Siska Mitria Nova (Institut Seni Indonesia Padangpanjang, 2022)
This research was conducted to increase students' creativity in utilizing aluminum waste for metal crafts at SMA Negeri 1 Panyabung Utara. The main source of problems in research is that students tend to be more passive and less creative, so that they are constrained in generating ideas for metal work. This study aims to increase students' creativity by utilizing aluminum waste and to find out the form of metal crafts produced by utilizing aluminum waste with press carving and filigree techniques. Data collection techniques in this study are active participation observation techniques, interviews and documentation. The data analysis technique uses descriptive qualitative analysis. The results of the study proved that there was an increase in the creativity of class XI students in making various metal craft products. To increase students' creativity in utilizing aluminum waste, several important stages are carried out, namely sorting materials, preparing equipment, making designs/sketches, the creative process of making decorative and functional metal craft products. In addition, to measure students' abilities can be seen based on creativity in designing works, perseverance in working on works and students' skills in making works. Efforts are made to increase student creativity, namely by providing motivation using varied learning media and displaying visual forms in the form of videos of metal craft work processes and photos of examples of metal craft products.